Morphology and fertility evaluation of soils from different geological materials for agricultural production in Southeastern Nigeria - Chinyere Blessing Okebalama; Felix Chikaizu Anih; Chukwuebuka Edwin Awaogu (Technology in Agronomy)
Knowledge of the properties of soils overlain by different geological materials is a fundamental decision-making tool for land suitability evaluation and soil fertility management. The morphological and physiochemical properties of soils overlying false-bedded sandstone (Pedon I) and upper coal measure (Pedon II) in Nsukka, Nigeria were investigated. Field studies involving excavation, delineation, description, and sampling were designed to determine the potential and limitations of each pedon species for agricultural production. Morphologically, both pedons were generally deep (> 150 cm), coarse-textured, and had darker topsoil than subsoil. The soils were predominately single-grained and crumbly, except for the structureless lower horizon of Pedon I. Pedon I had a uniform loamy sand texture, while Pedon II had an irregular loamy sand texture over sandy loam and sandy clay loam, with a silt:clay twice that of the former. A higher saturated hydraulic conductivity characterized Pedon I, while higher percentage aggregate stability and mean weight diameter characterized Pedon II. Both pedons were moderately to slightly acidic and had similar bulk density and total porosity, including N content. However, the organic carbon, available P, and exchangeable base contents were higher in Pedon II than in Pedon I. While favorable pH, organic matter, total N, and available P represent the potential of Pedon II for agricultural production, P and K are the main potentially limiting nutrients in Pedon I. Therefore, Pedon II is more favorable for crop production than Pedon I. Sustainable agricultural production on Pedon II would consequently require maintaining soil fertility through standard fertilization, as opposed to multiple fertilization in Pedon I.